Conceptual Metaphors in Psychotherapeutic Discourse (Using the Example of the Works of Art by Irwin Yalom and Ken Kesey) - I. V. Shugaylo (Дискурс, 2024)
Introduction. The article discusses the role and features of the conceptual metaphor in psychotherapeutic dis-course using the examples of fiction works by Irwin Yalom “The Schopenhauer Cure”, “Mommy and the Meaning of Life” and Ken Kesey “Over the Cuckoo's Nest” (translated by 2003 by D. Shepelev). The purpose of the article is to illustrate the metaphorical language of psychotherapeutic discourse (PD), involved in the fiction works. The widespread use of metaphor makes it possible to distinguish PD into an independent one. The relevance of linguistic analysis lies in expanding the language of discourses of helping professions.Methodology and sources. The article is based on the provisions of the theory of conceptual metaphor formulated by J. By Lakoff and M. Johnson. The methodological basis of the analysis are the works about PD and the metaphorical language of psychotherapy (I.V. Karasik, A.R. Markin, M.S. Grineva, E.V. Ermolaeva, etc.). Results and discussion. The article describes the characteristics of PD, describes the types of conceptual metaphors that are used in psychotherapeutic discourse based on the analysis of the fiction works. Among the main conceptual metaphors are the metaphors  “dispute is war”, “time is money”, “psyche as a machine”, orientation metaphors, where UP is associated with the concept of mental health, well-being, altruism, strength, high status, rationality, and DOWN  – with images of illness, failure, low social status, emotionality. Conclusion. The study shows the specifics of PD, primarily related to its metaphorical language. The examples of the conceptual metaphors highlighted by J. By Lakoff and M. Johnson illustrate the specific feature of PD of I. Yalom and K. Kesey.